Dziecko na wybranych przedstawieniach ikonograficznych Michała Stachowicza (1768–1825) - Kabacińska, Katarzyna (Wydawnictwo Naukowe UAM, 2010)
Basing on the reflections concerning the socio-political situation at the turn of the eighteenth and nineteenth centuries and its impact on art (especially painting), the author shows how the little-nown artist in Cracow, Michal Stachowicz depicts a child on his historical and realistic paintings as well as other works of art. One can distinguish 5 types of depicting a child: the child as an observer of political events, a participant in rituals, a peasant child, children's games and portraits.
A child in Michał Stachowicz’s selected iconographic portraits